A Study on Synthesis of Azole Derivatives Optimized for Anticancer Activity - Kumar, Mohit; Choudhary, Richa; Yeasmin, Luxmi; Singh, Shweta; Mishra , Kusum Lata; Singh, Aniruddh Dev; Kumari , Archana; Sundriyal , Anupriya (Journal of Neonatal Surgery, 2025)
Cancer is still the main reason for death volumn in the whole world, this promotes us to create new drugs that are stronger and very specific. This study seeks to construct a highly diversified library of new azole molecules and establish the therapeutic value of these drugs in the treatment of cancer patients. The principal end equally is to synthesize and design the compounds, evaluate their action against some kind of cancer cell lines, find the reliable structure-activity relationships and investigate the mechanisms of bioactivity. The possibility of applying that avenue on the treatment with azoles as base scaffolds to form an entirely new type of highly selective anticancer agents could come strongly from this work. Moreover, these findings will add to existing knowledge that should help with directing a more effective and successful development of next generation azole-like drugs in the future.